2012
DOI: 10.1094/php-2012-0618-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geosmithia morbida Isolate and Temperature on Canker Development in Black Walnut

Abstract: Thousand cankers disease of black walnut (Juglans nigra) is the result of aggressive feeding by the walnut twig beetle (Pityophthorus juglandis) and extensive cankering around beetle galleries caused by the fungus Geosmithia morbida. We developed a consistent, reproducible inoculation technique to screen black walnut trees for their reaction to canker development following inoculation with G. morbida. Canker areas in one-year-old trees were not affected by the location on the stem that inoculations were made. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…These results support previously observed differences in canker formation among J. nigra families following inoculation with G. mórbida (7,8). All J. nigra tested developed cankers following inoculation with G. tnorbida and it was the most susceptible of the walnut species.…”
Section: Discussionsupporting
confidence: 91%
“…These results support previously observed differences in canker formation among J. nigra families following inoculation with G. mórbida (7,8). All J. nigra tested developed cankers following inoculation with G. tnorbida and it was the most susceptible of the walnut species.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the substrate specificity of bark beetles and Geosmithia associates to their respective plant hosts [56], and the highly diverse and complex genetic structure in G. morbida that we and others [10,26,27] have observed, it is unlikely that the current TCD epidemic was a result of a new association between the WTB and G. morbida.…”
Section: Isolates and Genetic Diversitymentioning
confidence: 71%
“…Previous studies have indicated that the fungus is genetically complex [10,26]. Freeland The main objective of our study was to determine the diversity and spatial pattern of G. morbida haplotypes collected widely and intensively from both native and introduced Juglans and Pterocarya hosts in various locations in the USA.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptible hosts belong to the genera Juglans and Pterocarya ( J. ailantifolia , J. californica , J. cinerea , J. hindsii , J. major , J. mandshurica , J. microcarpa , J. mollis , J. nigra , J. regia , J. hindsii × J. regia , J. nigra × J. hindsii , J. cinerea × J. ailantifolia , J. nigra × J. regia , P. fraxinifolia , P. rhoifolia and P. stenoptera ; Seybold et al ., ; Serdani et al ., ; Utley et al ., ). Furthermore, susceptibility and intensity of symptoms varies among species (with J. nigra being the most susceptible) and individuals of the same species (Tisserat et al ., ; Freeland et al ., ; Utley et al ., ).…”
Section: The Hostsmentioning
confidence: 98%